Invasive bullfrogs as predators in a Neotropical assemblage: What frog species do they eat? - Boelter, Ruben Alexandre; Kaefer, Igor L.; Both, Camila; Cechin, Sônia Zanini (Animal Biology, 2012)
Anurans are important prey for the American bullfrog Lithobates catesbeianus, but field assessments of its diet in the context of a local prey assemblage are lacking. We aimed to identify the frog species consumed by an invasive bullfrog population in subtropical South America, and to assess their relative importance among other types of prey. Characterization of the frog assemblage in the study area also allowed us to calculate the degree of electivity of the recorded anuran prey, in order to gain insight regarding bullfrog feeding preferences and to test if the bullfrog prey composition differed from a random sample of the assemblage. A total of 32.6% of the bullfrogs had at least one anuran in the stomach contents, and post-metamorphic anurans represented 49.1% of the relative prey importance for adult bullfrogs. Anurans were preyed on by all size classes, and constituted the volumetrically most important prey category in the diet of individuals heavier than 100 g. Cycloramphidae, Hylidae and Leiuperidae were positively selected, and Hypsiboas pulchellus and Physalaemus cuvieri were the species most often taken. We found a low occurrence of cannibalism, despite the high density of bullfrogs at the study site. Our results showed that the degree of electivity differed among bullfrog prey types, suggesting that some frog species may be preyed on in a higher proportion than their relative abundance in the assemblage. Testing the clues provided by this assemblage-level approach may lead to a better assessment of the interactions between bullfrogs and the native frog fauna. © 2012 Koninklijke Brill NV, Leiden.
Keywords: Biological Invasion; Cannibalism; Diet; Frog; Invasive Species; Native Species; Neotropic Ecozone; Predation; Predator; Relative Abundance; Stomach Content; Subtropical Region; South America